Preparation and Characterization of Ibuprofen Containing Nano-Embedded-Microparticles for Pulmonary Delivery - Petra Party; Márk László Klement; Piroska Szabó-Révész; Rita Ambrus (Pharmaceutics, 2023)
A fatal hereditary condition, cystic fibrosis (CF) causes severe lung problems. Ibuprofen (IBU), a non-steroidal anti-inflammatory drug, slows the progression of disease without causing significant side effects. Considering the poor water-solubility of the drug, IBU nanoparticles are beneficial for local pulmonary administration. We aimed to formulate a carrier-free dry powder inhaler containing nanosized IBU. We combined high-performance ultra-sonication and nano spray-drying. IBU was dissolved in ethyl acetate; after that, it was sonicated into a polyvinyl alcohol solution, where it precipitated as nanoparticles. Mannitol and leucine were added when producing dry particles using nano-spray drying. The following investigations were implemented: dynamic light scattering, laser diffraction, surface tension measurement, scanning electron microscopy, X-ray powder diffraction, differential scanning calorimetry, Fourier-transform infrared spectroscopy, in vitro dissolution test, and in vitro aerodynamic assessment (Andersen Cascade Impactor). The particle diameter of the IBU was in the nano range. The spray-dried particles showed a spherical morphology. The drug release was rapid in artificial lung media. The products represented large fine particle fractions and proper aerodynamic diameters. We successfully created an inhalable powder, containing nano-sized IBU. Along with the exceptional aerodynamic performance, the ideal particle size, shape, and drug-release profile might offer a ground-breaking local therapy for CF.